1987
DOI: 10.1203/00006450-198705000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Recumbent, Ambulatory, and Postexercise Proteinuria in the Adolescent

Abstract: ABSTRACT. To better characterize the effects of body position and exercise on urinary protein excretion, carefully defined random urine samples were obtained during recumbency and following both ambulation and exercise in healthy adolescent student athletes. Albumin, lysozyme, and N-acetyl-B-D-glucosaminidase were measured in all samples. Glomerular permeability and tubular function were assessed using the urinary albumin creatinine ratio (UAlb/UCr), the urinary lysozyme creatinine ratio ( U L~/ U~) , the urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Creatinine, lysozyme and albumin were mea sured in all samples, and endogenous creatinine clearance (Ccr) was used as a measure of glomerular filtration rate. Creatinine was measured using a true creatinine method [16], lysozyme by an im proved turbidimetric technique [17] and albumin using a fluorescent immunoassay technique [18], as previously reported [19],…”
Section: Methodsmentioning
confidence: 99%
“…Creatinine, lysozyme and albumin were mea sured in all samples, and endogenous creatinine clearance (Ccr) was used as a measure of glomerular filtration rate. Creatinine was measured using a true creatinine method [16], lysozyme by an im proved turbidimetric technique [17] and albumin using a fluorescent immunoassay technique [18], as previously reported [19],…”
Section: Methodsmentioning
confidence: 99%
“…Past studies have shown a similar variation in ACR levels between recumbency and ambulation or between rest and physical activity [13,23]. In a previous study on orthostatic proteinuria [24] in this cohort of subjects we found that measured CrCl was higher during the daytime compared to the night and a higher CrCl was associated with an increased risk of orthostatic proteinuria.…”
Section: Discussionmentioning
confidence: 80%
“…In the past there has been conflicting findings regarding a gender difference in albumin excretion. Several studies have shown a higher ACR in girls compared to boys in both 24-hour and diurnal samples [13,23,25]. Houser found a higher ACR in girls only in upright or post exercise urine [23] but not supine samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary protein excretion is reportedly lower in both males and females in the recumbent posture and rises in the upright posture and after exercise [7][8][9]. Although girls are known to have slightly higher protein excretion at night compared to boys, this difference is not significant [10].…”
Section: Discussionmentioning
confidence: 88%